El trasfondo de un caso de violencia en el Quito de 1731: la actuación de Monteserín y su grupo contra María Salazar - Ramos Gómez, Luis (Revista Complutense de Historia de América, 2001)
On Good Friday of 1731, at Saint Francis Church in Quito, a trivial event happened between Antonia Mojardin and Maria Salazar, which ended in an agression on the latter. It seemed that the people who participated in this fight were relatives of Antonia, but the analysis of the documentation proves that there was a powerful group behind it, which was probably already led by Simon de Monteserin. The influence of this power group caused the Real Acuerdo to act judicially to punish the incident and to send the case file to the Consejo de Indias to prevent the people who were fined from twisting the facts in their appeal.
Keywords: Elites; network; violence; gender; daily life; Ecuador; 1731